Stochastic Time Series Analysis for Milk Production in Tamil Nadu - P. Pushpa; T. Jai Sankar (Utilitas Mathematica, 2025)
"This study presents a stochastic time series analysis for milk production in Tamil Nadu from 1978 to 2022. The increasing demand for milk and dairy products necessitates a thorough understanding of production trends and patterns in the region. Through rigorous data collection and preprocessing, this study identifies non-seasonal components influencing milk production. ARIMA (0,1,2) model is selected on the basis of its optimal fit, as determined by Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC). The model captures the underlying stochastic processes governing production fluctuations and provides reliable forecasts for future milk yield. The result indicates a significant upward trend in milk production, with periodic fluctuations that align with climatic and economic factors. The findings highlight the importance of strategic planning in dairy production to meet growing demands and ensure sustainable growth in Tamil Nadu's dairy sector. This research contributes valuable insights for policymakers and stakeholders aiming to enhance milk production efficiency and food security in the region."